Dietary exposure of the water flea Daphnia galeata to microcystin-LR - Eun-jeong Kim; Donggu Jeon; Yeon-jeong Park; Hyunmin Woo; Seong-il Eyun (Animal Cells and Systems)
Harmful substances like the cyanotoxin microcystin-leucine-arginine (MC-LR) are commonly found in eutrophic freshwater environments, posing risks to aquatic organisms. The water flea, Daphnia, is a well-established model organism for environmental toxicology research. Nevertheless, there is currently insufficient research on the genes that respond to MC-LR in Daphnia galeata. This study aimed to gain insights into the notable genes that react significantly to MC-LR. In this study, we generated an extensive RNA-Seq sequences isolated from the D. galeata HK strain, Han River in Korea. This strain was nourished with a diet of the green microalga Chlorella vulgaris and treated with pure MC-LR at a concentration of 36 ug/L. The transcriptome profile in response to the MC-LR treatment was obtained and 336 differentially expressed genes were subjected to Gene Ontology (GO) and euKaryotic Orthologous Groups of proteins analyses. GO enrichment analysis showed that chemical stimulus, amino sugar metabolic and catabolic process, oxidative stress, and detoxification were highly enriched, in reverse, proteolysis and fucosylation were underpresented. Detoxification process related genes such as peroxidase-like, chorion, and thyroid peroxidase-like were enriched for eliminating or neutralizing MC_LR from an organism's body. Furthermore, functional protein classification revealed an upregulation of lipid and inorganic ion transport processes, while amino acid and carbohydrate transport processes were found to be downregulated. These findings offer insights into how organisms respond to ecotoxic stimuli, providing valuable information for understanding adaptation or defense pathways.